Brexit, Archaeology and Heritage: Reflections and Agendas. Issue 1 (20th December 2017) - Gardner, Andrew; Harrison, Rodney
Abstract : This brief reflection considers some of the inter-relationships of, and implications for, archaeology and heritage in the narrow majority 'Leave' vote in the 2016 referendum on the withdrawal of the United Kingdom from the European Union, and the subsequent invocation of Article 50 of the Treaty of the European Union by Theresa May's administration in March 2017. We argue that heritage and archaeology were intimately implicated in the referendum result, and have and continue to play an important role in the rise of what have been termed 'new nationalisms' in Europe. We aim here to consider some of the ways in which this might be said to be the case, and to begin to explore what an emerging Brexit, archaeology and heritage research agenda might look like. In doing so, we aim to engage with a broader popular critique against 'expertise' and to forge a new role for research in archaeology and heritage studies which embeds itself within the very political context it seeks to study.